PENGARUH KUALITAS LAYANAN, HARGA, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN SEBLAK MANTAN JOMBANG - Mariyanti Mariyanti; Siti Nur Qomariyah (Gapenas Publisher, 2023)
This study looked at location, cost, product quality, and service quality. The participants in this study were students at KH universities. A. Wahab Hasbullah Jombang, to start. The study's findings support the notion that there is no substantial relationship between location and purchase decisions, nor is there any correlation between location and the quality of services rendered by personnel or the price charged by Seblak Ex. It is advised that seblak business owners consider environmental factors such as the state of the neighborhood surrounding the business location, the comfort and safety of the establishment, and easy access to customers when choosing a business location because business location affects consumer purchasing decisions. The study's findings suggest that there are still other variables that may influence how much seblak ex jombang would pay for a product and how good the service will be. It is advised that Seblak ex-jombang culinary entrepreneurs conduct a direct survey of customers regarding the evaluation of purchasing decisions made by consumers on service quality, price, product quality, and business location based on buyer perceptions so that seblak ex-jombang entrepreneurs can make strategies to increase their business. This is in addition to the quality of the product and the location. based on the traits of the customers that make up their target market